KERUSAKAN TEGAKAN TINGGAL AKIBAT PEMANENAN KAYU PADA HUTAN TROPIS BERBUKIT DI KALIMANTAN TENGAH - Soenarno; Wesman Endom; Sofwan Bustomi (BRIN Publishing, 2017)
One indicator of sustainable forest management is the minimum impact of residual stand damage caused by timber harvesting activities. This paper examines stand damage due to timber harvesting on hilly tropical forest, Central Kalimantan. The study was carried out using samples plot of 200 m x 100 m that was systematically placed on three selected cutting plots with different chainsaw operators working experience. Results showed that the degree of residual stands damage due to timber harvesting ranged between 19.37 – 34.9% with an average of 24.37% categorized as light stand damage. The average stands damage due to felling was 16.27% and skidding was 8.1%. Unexperienced chainsaw operators tend to cause greater damage than well trained chainsaw. Type of residual damage due to the felling on either sloping, rather steep or steep terrain was dominated by broken tree trunks. The most common type of residual stand damage due to skidding was the collapsed or tilted trees. The residual stand damage due to timber harvesting could be reduced by imposing intensive supervision in the felling sites and provide training and/or refresher to chainsaw and skidding tractor operators especially on cutting technique and environmentally friendly skidding.